2015
DOI: 10.1002/arch.21250
|View full text |Cite
|
Sign up to set email alerts
|

THE ENDOPARASITOID Pteromalus puparum INFLUENCES HOST GENE EXPRESSION WITHIN FIRST HOUR OF PARASITIZATION

Abstract: The small cabbage butterfly, Pieris rapae, is an important pest of cruciferous corps, and Pteromalus puparum is a predominant pupal endoparasitoid wasp of this butterfly. For successful development of parasitoid offspring, female parasitoids usually introduce one or several kinds of maternal factors into the hemocoels during oviposition to suppress host immunity. To investigate the early changes in host immune-related genes following parasitization, we analyzed transcriptomes of parasitized and unparasitized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…OfSP13 is the best reciprocal hit to PrPAP1 when reciprocal blastn was performed between O. furnacalis (50) and P. rapae transcriptome (33). OfSP13 has already been demonstrated to cleave PPO into PO and play an important role in PPO activation (44,51).…”
Section: Pps1v Inhibits O Furnacalis Ppo Activation Via a Complex Wimentioning
confidence: 99%
See 1 more Smart Citation
“…OfSP13 is the best reciprocal hit to PrPAP1 when reciprocal blastn was performed between O. furnacalis (50) and P. rapae transcriptome (33). OfSP13 has already been demonstrated to cleave PPO into PO and play an important role in PPO activation (44,51).…”
Section: Pps1v Inhibits O Furnacalis Ppo Activation Via a Complex Wimentioning
confidence: 99%
“…Other virulence factors found in some parasitoids, such as PDVs, virus-like particles, or teratocytes, have not been recorded in P. puparum (29). As the major maternal virulence factor in P. puparum, P. puparum venom regulates host development and metabolism (30) and suppresses cellular (27,28,31) and humoral immunity of the host (32)(33)(34). Here we report a serpin gene with 16 predicted splicing isoforms in P. puparum and show that one of these isoforms is a venom protein, which inhibits host PPO activation by forming complexes with host hemolymph proteinases.…”
mentioning
confidence: 99%
“…In the present study, PRR transcripts encoding PGRPs, βGRPs, CTLs, and Dscam were downregulated in parasitized G. qinghaiensis pupae. The expression levels of PGRPs and βGRPs are downregulated in P. rapae pupae after 1 hr of parasitoid attack (Y. Zhu et al, ). In contrast, J. Y. Zhu et al () found that the expression of both PGRP‐ and βGRP‐encoding genes in Tenebrio molitor is upregulated after parasitization by Scleroderma guani .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported changes in host transcriptional profiles after parasitization and identified many characteristic genes related to parasitization in parasitic wasps and hosts. Y. Zhu et al () used RNA‐Seq to analyze changes in the immune‐related gene expression profile in P. rapae parasitized early by P. puparum . Wu et al () applied comparative transcriptome analyses using the RNA‐Seq in Chilo suppressalis parasitized by Cotesia chilonis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation